1D ZnFe2O4 nanorods coupled with plasmonic Ag, Ag2S nanoparticles and Co-Pi cocatalysts for efficient photoelectrochemical water splitting. (26th July 2019) - Lan, Yayao; Liu, Zhifeng; Liu, Gang; Guo, Zhengang; Ruan, Mengnan; Rong, Hui; Li, Xifei
Abstract: Improving the absorption of visible light, accelerating the separation of carries and reducing the recombination of electron-hole pairs are critical to enhance photoelectrochemical (PEC) performance of ZnFe2 O4 . Herein, the ZnFe2 O4 /Ag/Ag2 S films are firstly prepared with a photocurrent density of 0.91 mA/cm 2 at 1.23 V vs. RHE, which is 9.10 times higher than that of pristine ZnFe2 O4 (0.10 mA/cm 2 at 1.23 V vs. RHE). On the basis, Co-Pi cocatalyst is deposited on ZnFe2 O4 /Ag/Ag2 S to further optimize PEC performance of ZnFe2 O4, the photocurrent density of ZnFe2 O4 /Ag/Ag2 S/Co-Pi is 1.18 mA/cm 2 at 1.23 V vs. RHE. The improved PEC performance of ZnFe2 O4 /Ag/Ag2 S/Co-Pi films could be attributed to: (i) fast transmission of electron-hole pairs owing to 1D ZnFe2 O4 NRs; (ii) surface plasmon resonance (SPR) effect of Ag nanoparticles; (ⅲ) visible light absorption is improved by sensitization of Ag2 S nanoparticles; (ⅳ) Co-Pi cocatalyst decreases the recombination of electron-hole pairs by capturing holes. This work provides new insights for metal plasmas, sensitizers and cocatalysts synergistically modify photoanodes for efficient PEC water splitting. Graphical abstract: Image 1 Highlights: 1D ZnFe2 O4 coupled with plasmonic Ag, Ag2 S NPs and Co-Pi co-catalyst for PEC water splitting. ZnFe2 O4 /Ag/Ag2 S films are prepared firstly via hydrothermal, chemical water bath and SILAR. ZnFe2 O4 /Ag/Ag2 S films are further optimized by depositing Co-Pi co-catalyst. ZnFe2 O4 /Ag/Ag2 S/Co-Pi could be used as photoanodes for photoelectrochemical water splitting. Efficient performance owing to excellent light-harvesting, fast electron-hole pairs separation.